Synthesis of Cu xO(x = 1,2)/amorphous compounds by dealloying and spontaneous oxidation method - Wang,Zhifeng (2014)
Cu xO(x = 1,2)/amorphous compounds have been successfully synthesized by chemical free dealloying and spontaneous oxidation method. Technological parameters, such as the acid concentration and dealloying time strongly influence the crystal type, size and morphology of coppery oxide. The further study shows that with the increase of HCl concentration, the surface coverage rate of Cu2O micro-flowers increases and the sizes of Cu2O micro-flowers get bigger. Moreover, it is observed that cracks are formed on the etched ribbon surface and plentiful Cu2O/CuO particles grow up from these crack walls if the dealloying time extends to long enough. Considering many fascinating properties of Cu2O/CuO particles and the amorphous alloy carrier, potential application fields of these amazing compounds will be developed in future.